Piezoelectric thick film micro-actuators for computer hard disk drives applications - Zhang, Zhe. (2008)
The storage capacities in magnetic hard disk drives are increasing very rapidly, and data is recorded in even narrower tracks, which must be followed with extreme precision. An advanced storage device having 7000 tracks per inch (tpi) today will have 20 to 25 ktpi by the end of this century. This places extreme requirements on the track following actuator system which brings the head to the data track and maintains the head over the track. A two-stage servo control system is required to achieve the track following in increasing densities of hard disk, and the piezoelectric micro-actuator has been identified as one of the most promising candidate.